Method for reducing glue discharging temperature of aluminum nitride ceramic
By using specific types of binders and plasticizers and performing step-by-step heating and glue discharge in a nitrogen environment, the problem of high glue discharge temperature of aluminum nitride ceramics is solved, preventing electrode corrosion and improving product quality and consistency.
Patent Information
- Application Number
- CN202411222871.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-02-21
AI Technical Summary
The glue discharge temperature of existing aluminum nitride ceramics is high, resulting in corrosion and uneven color problems during subsequent sintering and molding inspection.
The glue discharge temperature is reduced by preparing specific types of adhesives and plasticizers, including PVB-type adhesives and acrylic adhesives, and performing step-up heating and removal in a nitrogen environment.
It effectively reduces the glue discharge temperature of aluminum nitride ceramics from 390℃ to 410℃, prevents electrode oxidation and carbonization and corrosion under high temperature conditions, improves the consistency of product test data and design, and reduces the generation of defective products.
Smart Images

Figure CN119490358A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrostatic chucks, and in particular to a method for reducing the debinding temperature of aluminum nitride ceramics. Background Art
[0002] There are two ways to form aluminum nitride ceramic green bodies: tape casting and spray granulation. Tape casting is to scrape and dry the slurry on the carrier, and form a membrane of the required thickness under the action of binders, plasticizers and other additives. The process is batching, ball milling, discharging, degassing, tape casting, lamination, debinding, and sintering. Spray granulation is to make the slurry rotate at high speed in the spray granulation tower atomizer and dry at high temperature in the tower, so that small particles of powder form large solid spheres under the action of binders, dispersants and other additives and the surface tension of the slurry itself. The process is batching, ball milling, discharging, spray granulation, dry pressing, debinding, and sintering. Both processes involve: the selection of binders, the matching of plasticizers, and the matching of debinding curves. However, the matching degree of the debinding curve is related to the selection of binders and plasticizers; the formulation of equipment parameters is related to the process parameters and equipment process capabilities of each enterprise.
[0003] The types of adhesives currently used are basically PVB and acrylic, and the plasticizers are matched with them. The debonding temperature of the adhesive and plasticizer is: 500℃~750℃. The temperature is relatively high and there is a slight residue, which leads to corrosion and uneven color during subsequent sintering molding inspection. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for reducing the debinding temperature of aluminum nitride ceramics to solve the problem raised in the background technology.
[0005] In order to solve the above technical problems, the technical solution of the present invention is:
[0006] A method for reducing the debinding temperature of aluminum nitride ceramics, the method comprising:
[0007] Prepare binder and plasticizer:
[0008] Prepare the PVB adhesive, acrylic adhesive, and plasticizer to be used, which:
[0009] The PVB adhesives are: B30H and B60H.
[0010] The acrylic adhesives are: A118, R24E and KC-1350. The acrylic adhesive A118 is a copolymer of methyl methacrylate and ethyl acrylate, the acrylic adhesive R24E is a copolymer of methyl methacrylate and n-butyl methacrylate, and the acrylic adhesive KC-1350 is a copolymer of alkyl methacrylate and n-butyl methacrylate.
[0011] Plasticizers are RS107 and DOA;
[0012] Determine loss on ignition:
[0013] Take 2g of acrylic adhesive and PVB adhesive and put them into a crucible, debind them in a nitrogen environment at a temperature of 390-410℃, and determine the ignition loss;
[0014] Debonding rate of casting method:
[0015] The ingredients are prepared in the required proportions, and the casting is performed to determine the strength and toughness of the cast sheet. The cast sheet is laminated to a thickness of 2 cm, and then the binder is removed. After the binder is removed, the binder removal rate under this method is determined;
[0016] Debinding rate of spray granulation method:
[0017] Mix the ingredients according to the required proportion, perform spray granulation, determine the sphericity and particle size grading, determine the strength after dry pressing, then perform binder removal, and determine the binder removal rate after binder removal;
[0018] Determining the binder and plasticizer suitable for preparing aluminum nitride ceramics by two processes can reduce the debinding temperature of aluminum nitride ceramics and improve the debinding rate.
[0019] Preferably, in the step of determining the ignition loss, 2 g of acrylic binder and PVB binder are placed in a small crucible, and the temperature is gradually increased to 400°C by a step-by-step heating method, with a heating rate of 0.5-1.5°C / min. The temperature is kept warm for 30-60 min every time the temperature increases by 50°C. When the temperature reaches 400°C, it is kept warm for 3-12 h. During the heating, the debinding furnace is filled with N2. After the debinding is completed, the ignition loss is determined.
[0020] Preferably, in the binder removal rate step of the casting method, the ingredients include: binder: 8% to 12% wt, solvent: 30% to 50% wt, dispersant: 0.5% to 2% wt, plasticizer: 4% to 6% wt.
[0021] Preferably, in the debinding rate step of the spray granulation method, the ingredients include: binder: 1% to 5% wt, solvent: 20% to 40% wt, dispersant: 0.5% to 2% wt, plasticizer: 0.5% to 2% wt.
[0022] The above technical solution has the following beneficial effects:
[0023] There are electrodes in the aluminum nitride electrostatic chuck, which are easily oxidized and carbonized and corroded under high temperature conditions, resulting in increased resistance and shortened service life. Therefore, in the medium and low temperature debinding, the debinding temperature of 500℃~750℃ in the existing technology is reduced to 390~410℃, which can effectively prevent the occurrence of this problem, thereby making the product test data consistent with the design and reducing the generation of defective products. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a picture of the debonding test of the pvb adhesive B30H of the present invention;
[0025] Figure 2 This is a picture of the debonding test of the pvb adhesive B60H of the present invention;
[0026] Figure 3 This is a picture of the adhesive removal test of the acrylic adhesive A118 of the present invention;
[0027] Figure 4 This is a picture of the adhesive removal test of the acrylic adhesive R24E of the present invention;
[0028] Figure 5 This is a picture of the adhesive removal test of the acrylic adhesive KC-1350 of the present invention. DETAILED DESCRIPTION
[0029] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0030] Example 1
[0031] A method for reducing the debinding temperature of aluminum nitride ceramics, comprising:
[0032] Prepare binder and plasticizer:
[0033] Prepare the PVB adhesive, acrylic adhesive, and plasticizer to be used, wherein:
[0034] PVB adhesives are: B30H and B60H,
[0035] The acrylic adhesives are: A118, R24E and KC-1350. The acrylic adhesive A118 is a copolymer of methyl methacrylate and ethyl acrylate, the acrylic adhesive R24E is a copolymer of methyl methacrylate and n-butyl methacrylate, and the acrylic adhesive KC-1350 is a copolymer of alkyl methacrylate and n-butyl methacrylate.
[0036] Plasticizers are RS107 and DOA;
[0037] Determine loss on ignition:
[0038] Take 2g of acrylic adhesive and PVB adhesive and put them into a crucible, heat it to 390-410℃ in a nitrogen environment to remove the binder, preferably 400℃ in a nitrogen environment to remove the binder, and determine the ignition loss;
[0039] Specifically, 2g of acrylic binder and PVB binder were weighed and placed in a small crucible, and the temperature was gradually increased to 400°C by a step-by-step heating method, with a heating rate of 0.5-1.5°C / min. The temperature was kept warm for 30-60min every time the temperature was increased by 50°C. When the temperature reached 400°C, it was kept warm for 3-12h. During the heating, the debinding furnace was filled with N2. After the debinding was completed, the loss on ignition was determined.
[0040] Debonding rate of casting method:
[0041] The ingredients are prepared in the required proportions, and the casting is performed to determine the strength and toughness of the cast sheet. The cast sheet is laminated to a thickness of 2 cm, and then the binder is removed. After the binder is removed, the binder removal rate under this method is determined;
[0042] The ingredients in the casting method include: binder: 8% to 12% wt, solvent: 30% to 50% wt, dispersant: 0.5% to 2% wt, plasticizer: 4% to 6% wt;
[0043] Debinding rate of spray granulation method:
[0044] Mix the ingredients according to the required proportion, perform spray granulation, determine the sphericity and particle size grading, determine the strength after dry pressing, then perform binder removal, and determine the binder removal rate after binder removal;
[0045] In the above-mentioned spray granulation method, the ingredients include: binder: 1% to 5% wt, solvent: 20% to 40% wt, dispersant: 0.5% to 2% wt, plasticizer: 0.5% to 2% wt;
[0046] Determine the binder and plasticizer suitable for preparing aluminum nitride ceramics by two processes, which can reduce the debinding temperature of aluminum nitride ceramics and improve the debinding rate;
[0047] There are electrodes in the aluminum nitride electrostatic chuck, which are easily oxidized and carbonized and corroded under high temperature conditions, resulting in increased resistance and shortened service life. Therefore, debinding at medium and low temperatures can effectively prevent this problem, so that the product test data is consistent with the design and the generation of defective products is reduced.
[0048] Example 2
[0049] A method for reducing the debinding temperature of aluminum nitride ceramics, comprising:
[0050] Prepare binder and plasticizer:
[0051] Prepare a PVB adhesive, an acrylic adhesive, and a plasticizer to be used, wherein the PVB adhesive is B30H and B60H, the acrylic adhesive is A118, R24E, and KC-1350, the acrylic adhesive A118 is a copolymer of methyl methacrylate and ethyl acrylate, the acrylic adhesive R24E is a polymerization of methyl methacrylate and n-butyl methacrylate, the acrylic adhesive KC-1350 is a polymerization of alkyl methacrylate and n-butyl methacrylate, and the plasticizers are RS107 and DOA;
[0052] Determine loss on ignition:
[0053] Take 2g of acrylic adhesive and PVB adhesive and put them into a crucible, heat it to 390℃ in a nitrogen environment to remove the adhesive, and determine the ignition loss;
[0054] Specifically, 2g of acrylic binder and PVB binder were weighed and placed in a small crucible, and the temperature was gradually increased to 390°C by a step-by-step heating method, with a heating rate of 0.5°C / min. The temperature was kept warm for 30min every time the temperature was increased by 50°C. When the temperature reached 390°C, it was kept warm for 3h. During the heating, the debinding furnace was filled with N2. After the debinding was completed, the ignition loss was determined.
[0055] Debonding rate of casting method:
[0056] The ingredients are prepared in the required proportions, and the casting is performed to determine the strength and toughness of the cast sheet. The cast sheet is laminated to a thickness of 2 cm, and then the binder is removed. After the binder is removed, the binder removal rate under this method is determined;
[0057] The ingredients in the casting method include: binder: 8%wt, solvent: 30%wt, dispersant: 0.5%wt, plasticizer: 4%wt;
[0058] Debinding rate of spray granulation method:
[0059] Mix the ingredients according to the required proportion, perform spray granulation, determine the sphericity and particle size grading, determine the strength after dry pressing, then perform binder removal, and determine the binder removal rate after binder removal;
[0060] In the above-mentioned spray granulation method, the ingredients include: binder: 1%wt, solvent: 20%wt, dispersant: 0.5%wt, plasticizer: 0.5%wt;
[0061] Determine the binder and plasticizer suitable for preparing aluminum nitride ceramics by two processes, which can reduce the debinding temperature of aluminum nitride ceramics and improve the debinding rate;
[0062] There are electrodes in the aluminum nitride electrostatic chuck, which are easily oxidized and carbonized and corroded under high temperature conditions, resulting in increased resistance and shortened service life. Therefore, debinding at medium and low temperatures can effectively prevent this problem, so that the product test data is consistent with the design and reduce the generation of defective products.
[0063] Example 3
[0064] A method for reducing the debinding temperature of aluminum nitride ceramics, comprising:
[0065] Prepare binder and plasticizer:
[0066] Prepare a PVB adhesive, an acrylic adhesive, and a plasticizer to be used, wherein the PVB adhesive is B30H and B60H, the acrylic adhesive is A118, R24E, and KC-1350, the acrylic adhesive A118 is a copolymer of methyl methacrylate and ethyl acrylate, the acrylic adhesive R24E is a polymerization of methyl methacrylate and n-butyl methacrylate, the acrylic adhesive KC-1350 is a polymerization of alkyl methacrylate and n-butyl methacrylate, and the plasticizers are RS107 and DOA;
[0067] Determine loss on ignition:
[0068] Take 2g of acrylic adhesive and PVB adhesive and put them into a crucible, heat it to 410℃ and remove the adhesive in a nitrogen environment, preferably 400℃ and remove the adhesive in a nitrogen environment, and determine the loss on ignition;
[0069] Specifically, 2g of acrylic binder and PVB binder were weighed and placed in a small crucible, and the temperature was gradually increased to 410°C by a step-by-step heating method at a heating rate of 1.5°C / min. The temperature was kept for 60min every time the temperature was increased by 50°C. When the temperature reached 410°C, it was kept for 12h. During the heating, the debinding furnace was filled with N2. After the debinding was completed, the loss on ignition was determined.
[0070] Debonding rate of casting method:
[0071] The ingredients are prepared in the required proportions, and the casting is performed to determine the strength and toughness of the cast sheet. The cast sheet is laminated to a thickness of 2 cm, and then the binder is removed. After the binder is removed, the binder removal rate under this method is determined;
[0072] The ingredients in the casting method include: binder: 12%wt, solvent: 50%wt, dispersant: 2%wt, plasticizer: 6%wt;
[0073] Debinding rate of spray granulation method:
[0074] Mix the ingredients according to the required proportion, perform spray granulation, determine the sphericity and particle size grading, determine the strength after dry pressing, then perform binder removal, and determine the binder removal rate after binder removal;
[0075] In the above-mentioned spray granulation method, the ingredients include: binder: 5%wt, solvent: 40%wt, dispersant: 02%wt, plasticizer: 2%wt;
[0076] Determine the binder and plasticizer suitable for preparing aluminum nitride ceramics by two processes, which can reduce the debinding temperature of aluminum nitride ceramics and improve the debinding rate;
[0077] There are electrodes in the aluminum nitride electrostatic chuck, which are easily oxidized and carbonized and corroded under high temperature conditions, resulting in increased resistance and shortened service life. Therefore, debinding at medium and low temperatures can effectively prevent this problem, so that the product test data is consistent with the design and the generation of defective products is reduced.
[0078] Example 4
[0079] refer to Figure 1 , weigh 2g of PVB binder B30H and place it in a small crucible, gradually heat it to 400℃ by a step-by-step heating method, the heating rate is 0.5-1.5℃ / min, the heating rate is preferably 1℃ / min, keep warm for 30-60min every time the temperature rises by 50℃, preferably keep warm for 45min every time the temperature rises by 50℃, when the temperature rises to 400℃, keep warm for 3-12h, preferably keep warm for 7.5h, the debinding furnace is filled with N2 during the heating, and the loss on ignition is determined after the debinding is completed.
[0080] Example 5
[0081] refer to Figure 2 , weigh 2g of PVB binder B60H and place it in a small crucible, and gradually heat it to 400℃ using a step-by-step heating method. The heating rate is 0.5-1.5℃ / min, and the heating rate is preferably 1℃ / min. Keep warm for 30-60min for every 50℃ increase in temperature, and preferably keep warm for 45min for every 50℃ increase in temperature. When the temperature reaches 400℃, keep warm for 3-12h, and preferably keep warm for 7.5h. During the heating, the debinding furnace is filled with N2. After the debinding is completed, determine the loss on ignition.
[0082] Example 6
[0083] refer to Figure 3 , weigh 2g of acrylic binder A118 and place it in a small crucible, and gradually heat it to 400℃ using a step-by-step heating method. The heating rate is 0.5-1.5℃ / min, and the heating rate is preferably 1℃ / min. Keep warm for 30-60min for every 50℃ increase in temperature, and preferably keep warm for 45min for every 50℃ increase in temperature. When the temperature reaches 400℃, keep warm for 3-12h, and preferably keep warm for 7.5h. During the heating, the debinding furnace is filled with N2. After the debinding is completed, determine the loss on ignition.
[0084] Example 7
[0085] refer to Figure 4 , weigh 2g of acrylic adhesive R24E and place it in a small crucible, and gradually heat it to 400℃ using a step-by-step heating method. The heating rate is 0.5-1.5℃ / min, and the heating rate is preferably 1℃ / min. Keep warm for 30-60min for every 50℃ increase in temperature, and preferably keep warm for 45min for every 50℃ increase in temperature. When the temperature reaches 400℃, keep warm for 3-12h, and preferably keep warm for 7.5h. During the heating, the debinding furnace is filled with N2. After the debinding is completed, determine the loss on ignition.
[0086] Example 8
[0087] refer to Figure 5 , weigh 2g of acrylic binder KC-1350 and place it in a small crucible, and gradually heat it to 400℃ using a step-by-step heating method. The heating rate is 0.5-1.5℃ / min, and the heating rate is preferably 1℃ / min. Keep warm for 30-60min for every 50℃ increase in temperature, and preferably keep warm for 45min for every 50℃ increase in temperature. When the temperature rises to 400℃, keep warm for 3-12h, and preferably keep warm for 7.5h. During the heating, the debinding furnace is filled with N2. After the debinding is completed, determine the loss on ignition.
[0088] Under the conditions of Examples 1 to 5, the statistics of the binder removal rates are shown in Table 1:
[0089] Table 1:
[0090]
[0091] According to Table 1 above, the acrylic binder A118 and acrylic binder R24E have a binder removal rate greater than 99%, so these two binders are selected for the subsequent casting and spray granulation methods;
[0092] Example 9
[0093] Adopting acrylic adhesive A118 and acrylic adhesive R24E, the casting is carried out, and the ingredients in the casting method include: adhesive: 8% to 12% wt, solvent: 30% to 50% wt, dispersant: 0.5% to 2% wt, plasticizer: 4% to 6% wt;
[0094] The toughness of the cast sheet was determined after casting. When RS107 plasticizer was used, no cracks were found when using acrylic adhesive A118 and acrylic adhesive R24E, but curling was found when using DOA plasticizer. As for the difference between the debonding rate after lamination and the theoretical debonding rate, the difference between the debonding rate of acrylic adhesive A118 and the theoretical debonding rate was 0.1, and for acrylic adhesive R24E, the difference between the debonding rate of the adhesive and the theoretical debonding rate was 0.3. In summary, RS107 plasticizer and acrylic adhesive A118 are preferably used for preparing ceramics by casting method.
[0095] Example 10
[0096] The method adopts acrylic binder A118 and acrylic binder R24E to carry out a spray granulation method, wherein the ingredients include: binder: 1% to 5% wt, solvent: 20% to 40% wt, dispersant: 0.5% to 2% wt, plasticizer: 0.5% to 2% wt;
[0097] After spray granulation, the quality is judged according to the sphericity. The solid ball is qualified and the acrylic adhesive A118 is used. The morphology is qualified. As for the strength after pressing, neither the acrylic adhesive A118 nor the acrylic adhesive R24E has cracking. The debonding rates of the acrylic adhesive A118 and the acrylic adhesive R24E are 0.1. In summary, the acrylic adhesive A118 is used as the adhesive for the spray granulation method.
[0098] In summary, using A118 as a binder and RS107 as a plasticizer has the best matching degree among all processes.
[0099] The embodiments of the present invention are described in detail above with reference to the accompanying drawings, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the scope of protection of the present invention.
Claims
1. A method for reducing the debinding temperature of aluminum nitride ceramics, characterized in that: The method comprises: Prepare binder and plasticizer: Prepare the PVB adhesive, acrylic adhesive, and plasticizer to be used, wherein: PVB adhesives are: B30H and B60H, The acrylic adhesives are: A118, R24E and KC-1350. The acrylic adhesive A118 is a copolymer of methyl methacrylate and ethyl acrylate, the acrylic adhesive R24E is a copolymer of methyl methacrylate and n-butyl methacrylate, and the acrylic adhesive KC-1350 is a copolymer of alkyl methacrylate and n-butyl methacrylate. Plasticizers are RS107 and DOA; Determine loss on ignition: Take 2g of acrylic adhesive and PVB adhesive and put them into a crucible, debind them in a nitrogen environment at a temperature of 390-410℃, and determine the ignition loss; Debonding rate of casting method: The ingredients are prepared in the required proportions, and the casting is performed to determine the strength and toughness of the cast sheet. The cast sheet is laminated to a thickness of 2 cm, and then the binder is removed. After the binder is removed, the binder removal rate under this method is determined; Debinding rate of spray granulation method: Mix the ingredients according to the required proportion, perform spray granulation, determine the sphericity and particle size grading, determine the strength after dry pressing, then perform binder removal, and determine the binder removal rate after binder removal; Determining the binder and plasticizer suitable for preparing aluminum nitride ceramics by two processes can reduce the debinding temperature of aluminum nitride ceramics and improve the debinding rate.
2. The method for reducing the debinding temperature of aluminum nitride ceramics according to claim 1, characterized in that: In the step of determining the ignition loss, 2 g of acrylic binder and PVB binder are placed in a small crucible, and the temperature is gradually increased to 400°C by a step-by-step heating method, with a heating rate of 0.5-1.5°C / min. The temperature is kept warm for 30-60 minutes every time the temperature rises by 50°C. When the temperature reaches 400°C, it is kept warm for 3-12 hours. During the heating, the debinding furnace is filled with N2. After the debinding is completed, the ignition loss is determined.
3. The method for reducing the debinding temperature of aluminum nitride ceramics according to claim 1, characterized in that: In the step of the adhesive removal rate of the casting method, the ingredients include: Binder: 8% to 12% wt, solvent: 30% to 50% wt, dispersant: 0.5% to 2% wt, plasticizer: 4% to 6% wt.
4. The method for reducing the debinding temperature of aluminum nitride ceramics according to claim 1, characterized in that: In the binder removal rate step of the spray granulation method, the ingredients include: Binder: 1% to 5% wt, solvent: 20% to 40% wt, dispersant: 0.5% to 2% wt, plasticizer: 0.5% to 2% wt.